Uji Sitotoksik Ekstrak Etanol Kulit Buah Naga Merah (Hylocereus Polyrhizus) Dan Kulit Buah Naga Putih (Hylocereus Undatus) Terhadap Sel Kanker Payudara Mcf-7 - Fauzi, Niswatun Nurul, Maryati Ph.D., Apt (2017)
Previous experiment that red dragon fruit (Hylocereus polyrhizus) peel and white dragon fruit (Hylocereus undatus) peel possessed cytotoxic activity. The study was purposed to determine the cytotoxic effects of extract red dragon fruit (Hylocereus polyrhizus) peel and white dragon fruit (Hylocereus undatus) peel on breast cancer cells MCF-7 and to identify the compound in one of the extract as a potential anti breast cancer. Cytotoxic test was used by MTT assay 3- (4,5-dimetiltiazol-2-yl) -2,5-difeniltetrazolium bromide) method. The extract has a better IC50 value was tested by TLC (Thin Layer Chromatography) to know the potential of compounds as anti cancer. The results shows IC50 red dragon fruit (Hylocereus polyrhizus) peel is 392 835 µg/mL while white dragon fruit (Hylocereus undatus) peel is 186, 226 µg/mL. Based on the value, the extract has a low potential as anti-cancer on MCF-7 cells. The result shows compounds of white dragon fruit (Hylocereus undatus) peel is terpenoids, saponins, flavonoids and compound have a cytotoxic potency is terpenoids.